Case report: Colon ischemia and perforation as a result of Norovirus infection. (January 2021) - Beredjiklian, C.M.; Olf, M.; Abusaman, A.; Becker, R.; Jonescheit, J.
Highlights: Atypical Norovirus infection symptoms and course. Unusual diagnostics with CT findings: ischemia, pneumatosis intestinalis and perforation. Surgical Procedure: Resection with good surgical outcome. First case of its kind in Germany, first recommendations of how to approach atypical Norovirus infection. Abstract: Introduction: Norovirus (NoV) gastroenteritis has been documented as the worldwide leading cause of the majority of acute cases of viral gastroenteritis. Here, we present a Case of NoV that progressed into colon perforation. Presentation of case: A 47-year-old woman was admitted via the emergency unit with diarrhoea, lower abdominal pain, vomiting and fever. The virological testing of her stool revealed a NoV infection. The abdominal CT scan showed massive pneumatosis intestinalis. Following the scan findings, the patient was admitted for a diagnostic laparotomy the same day. A side-to-side ileosigmoidostomy was performed. We performed two clinical re-evaluations of the patient, the first one took place 2 weeks after we discharged the patient and another one-year later. The patient is in perfect health. Discussion: To the best of our knowledge and following a thorough bibliographical search, this is the first case report in Germany and the first case report of colon perforation due to NoV infection in adults in the European Union. Conclusion: A NoV infection could, along with the typical symptoms, indicate a life-threatening bowel ischemia and/or necrosis.